GPER1-mediated suppression of acute cellular rejection in murine cervical heart transplantation by estradiol - Yiwei Liu; Ran Wang; Bater Han; Benben Zhu; Yu Ma; Yongjun Yu; Lu Bai; Qiyou Wei; Pengjie Yang (Journal of Cardiothoracic Surgery)
Abstract Objective This study aimed to investigate the inhibitory effect of estradiol (E2) on acute cellular rejection following murine cervical heart transplantation and the role of G protein-coupled estrogen receptor 1 (GPER1). Method A murine cervical heart transplantation model was established and categorized into four groups: syngeneic group (C57BL/6 to C57BL/6), allogenic control group (BALB/c to C57BL/6), E2 group (BALB/c to C57BL/6), and E2 + G15 group (G15: one of GPER1 blocker) (BALB/c to C57BL/6). Survival time, pathological rejection grade, intimal hyperplasia area of coronary artery in donor heart, mRNA expression levels of TGF-β, IL-10, and Foxp3 in spleen, and protein expression levels of CD4 and CD25 in spleen membrane proteins, were compared among these groups. Results The syngeneic group showed 100% survival, while survival in the allogenic control group was significantly reduced. E2 treatment prolonged survival compared to the allogenic control group, but survival decreased with the addition of E2 + G15. Rejection was reduced in the E2 group compared to the allogenic control group, whereas the E2 + G15 group exhibited increased rejection compared to the E2 group. Intimal hyperplasia was absent in the syngeneic group, significant in the allogenic control group, reduced in the E2 group compared to the allogenic control group, but greater in the E2 + G15 group compared to the E2 group. The expression of IL-10, Foxp3, and TGF-β in the allogenic control group was higher than in the syngeneic group. In the E2 group, IL-10, Foxp3, and CD25 were higher than in the allogenic control group, while TGF-β and CD4 expression were lower. The E2 + G15 group had lower IL-10, Foxp3, and CD25 expression but higher TGF-β expression than the E2 group. Conclusion Severe acute cellular rejection was observed following murine cervical heart transplantation. E2 suppresses acute rejection by enhancing Treg cell expression, mediated by GPER1.